## Solving (k+1)(k-5) = 0 by Factoring

This equation is already in factored form, which makes solving for *k* very straightforward. Here's how we can solve it:

### Understanding the Zero Product Property

The **Zero Product Property** states that if the product of two or more factors is zero, then at least one of the factors must be zero.

In our equation, (k+1) and (k-5) are the factors.

### Solving for k

To find the values of *k* that make the equation true, we set each factor equal to zero and solve:

**Factor 1:**k + 1 = 0- Subtract 1 from both sides: k = -1

**Factor 2:**k - 5 = 0- Add 5 to both sides: k = 5

### Solutions

Therefore, the solutions to the equation (k+1)(k-5) = 0 are **k = -1** and **k = 5**.

**In summary, by using the Zero Product Property, we were able to quickly and easily find the solutions to the equation by setting each factor equal to zero and solving for k.**